Missio politica in missio Dei: Integrating politics into God’s eternal mission - Thinane, Jonas S. (Verbum et ecclesia, 2022)
The understanding of the missio Dei from the point of view of the International Missionary Conference in Willingen has rightly broadened the missiological horizon and promoted new approaches to God’s mission in the world. This conference abandoned the ecclesiological approach to mission and focused attention on God as the foundation or source of mission. Inherently, this new perspective opened the door for other human institutions, such as politics, to be seen as critical participants together with the churches in the missio Dei . Apart from the writings of Saayman and Reimer, not much scholarly work is carried out to further develop the framework of the missio politica as an important tool to enable an analysis of politics in accordance with total salvation as the ultimate goal of the missio Dei . Relying upon literary analysis, this contribution orients itself on such exclusive important works as a basis on which missio politica is strengthened as a missiological framework that examines politics in relation to the ultimate goal of the missio Dei . Intradisciplinary and/or interdisciplinary implications: This article presents research on the development of the missio politica framework in the field of missiology and highlights it as an important framework encompassing the scope of politics in relation to the eternal mandate of the missio Dei .